Effects of glucocorticoids on postoperative delirium in patients undergoing elective non-cardiac surgery:A systematic review and meta-analysis - Zicen Li; Jing Lu; Di Wang; Liping Han (Heliyon)
Background: Postoperative delirium (POD) is common postoperative complications in non-cardiac surgery. While delirium prophylaxis has not yielded unequivocal support. The clinical effects of glucocorticoids on POD remains unclear. Objective: To evaluate the effects of glucocorticoids on postoperative delirium (POD) in patients undergoing non-cardiac surgery. Design: Systematic review with meta-analysis. Methods: In strict accordance with the PRISMA statement, a systematic literature search was undertaken across PubMed, EMBASE, Web of Science and Cochrane Library databases in May 2023. We updated the search results on June 28, 2024. We used the Grading of the Recommendation Assessment, Development, and Evaluation (GRADE) system to evaluate the quality of evidence. Results: This meta-analysis included twelve randomized controlled trials involving 1044 participants undergoing non-cardiac surgery. Compared with the control group, glucocorticoids significantly reduced the incidence of POD in patients undergoing non-cardiac surgery (RR:0.50, 95%CI:0.41 to 0.60, P < 0.00001, I2 = 26 %, GRADE = high). Meanwhile, glucocorticoids was associated with reducing the severity of POD (RR: −0.67, 95%CI: −1.10 to −0.23, P = 0.003, I2 = 89 %, GRADE = low). However, there were no significant differences with regards to patients receiving antipsychotic drug (RR: 0.91, 95%CI:0.43 to 1.92, P = 0.80, I2 = 0 %, GRADE = moderate), length of hospital stay (RR: −0.52, 95%CI: −1.41 to 0.36, P = 0.24, I2 = 0 %, GRADE = moderate), 30-day postoperative mortality (RR: 0.70, 95%CI:0.23 to 2.15, P = 0.54, I2 = 0 %, GRADE = low) and postoperative infection (RR: 0.87 95%CI: 0.58 to 1.30, P = 0.50, I2 = 33 %, GRADE = moderate). Conclusions: This systematic review and meta-analysis suggests that glucocorticoids reduce the incidence of POD among adults and children undergoing non-cardiac surgery and mitigate the severity of POD in adults, which indicates that glucocorticoids exhibit preventive or therapeutic effects on POD. Registration: CRD42023426836 (PROSPERO).